Gibberellin Treatment Toward Off-crop Season as a Practical Tool to Increase Yield in ‘Orri’ Mandarin - Dor Haim; Itzhak Kamara; Michael Morozov; Avi Sadka (HortScience)
Multiannual fruit bearing in fruit trees varies from regular bearing, with an almost steady yield from season to season, to alternate bearing, during which a year with a high fruit load (on-crop) is followed by a year of a low fruit load (off-crop). ‘Orri’ mandarin [Temple (Citrus temple hort. ex Y. Tanaka) × Dancy (Citrus tangerine hort. ex Tanaka)] exhibits a nonregular bearing pattern: steady for a few years and alternate for others. In nonregular or alternate-bearing cultivars, fruit load is thought to regulate flowering induction and development negatively the following year. In citrus, the bud meristem develops into a leafless inflorescence (generative), leafy inflorescence (mixed type, containing leaves and flowers in various ratios), or vegetative shoot, or remains dormant. Mixed-type inflorescences contribute to most of the final yield. Gibberellins inhibit flowering when applied at relatively high concentrations during the flowering induction period in the winter, but they are suggested to induce yield when applied at relatively low concentrations. We determined the effect of mild gibberellin application in an off-crop year on the productivity of ‘Orri’ mandarin, and whether it occurs through the induction of mixed-type inflorescences. Low-concentration, low-frequency gibberellin treatments were applied to trees during the winter when fruit load was high, resulting in a greater number of mixed vs. generative inflorescences at anthesis. An average increase of 40% in fruit number and yield weight was recorded in off-crop seasons at harvest, whereas no change was recorded in on-crop seasons. We discuss treatment efficiency in on-crop and off-crop years as a practical tool for increasing yield in low-crop seasons of ‘Orri’ mandarin.